Advocacy coalitions and elite sport policy change in Canada and the United Kingdom - Green, M.; Houlihan, B. (International Review for the Sociology of Sport, 2004)
This paper explores the process of elite sport policy change in two sports (swimming and track and field athletics1) and their respective national sport organizations (NSOs) in Canada and national governing bodies of sport (NGBs) in the United Kingdom (UK). The nature of policy change is a complex and multifaceted process and a primary aim is to identify and analyse key sources ofpolicy change through insights provided by the advocacy coalition framework (ACF). In Canada, it is evident that the preoccupation with high performance sport over the past 30 years, at federal government level, has perceptibly altered over the past two to three years. In contrast, in the UK, from the mid-1990s onwards, there has been a noticeable shift towards supporting elite sport objectives from both Conservative and Labour administrations. Most notably, the ACF throws into sharp relief the part played by the state in using its resource control to shape the context within which debates on beliefs and values within NSOs/NGBs takes place. While the ACF has proved useful in drawing attention to the notion of changing values and belief systems as a key source of policy change, as well as highlighting the need to take into account factors external to the policy subsystem under investigation, potential additions to the framework`s logic are suggested for future applications.